2016
DOI: 10.1002/ccd.26653
|View full text |Cite
|
Sign up to set email alerts
|

Short‐versus long‐term Dual Antiplatelet therapy after drug‐eluting stent implantation in women versus men: A sex‐specific patient‐level pooled‐analysis of six randomized trials

Abstract: Short-term DAPT is associated with similar rates of MACE but lower risk of bleeding when as compared with prolonged DAPT. There was no significant difference between sexes in the population studied. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
2
15
0
1
Order By: Relevance
“…Our current analysis already involved participants with thrombocytopenia, and therefore, logically, longer duration of DAPT use might not be tolerable in similar patients following PCI. Another study showed short term DAPT use to be equally effective and safer compared to long term DAPT use following stents implantation with drug eluting stents [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current analysis already involved participants with thrombocytopenia, and therefore, logically, longer duration of DAPT use might not be tolerable in similar patients following PCI. Another study showed short term DAPT use to be equally effective and safer compared to long term DAPT use following stents implantation with drug eluting stents [30].…”
Section: Discussionmentioning
confidence: 99%
“…-They were literature reviews (3); -They were case studies 17; -They were based on thrombocytopenia after PCI and did not involve participants with thrombocytopenia at baseline (26); -They were letters of correspondence (4); -They were duplicated studies from several different search databases (30).…”
Section: Outcome Of the Search Process And The Selection Of Studiesmentioning
confidence: 99%
“…Gender was not a treatment modifier in terms of DAPT duration and men and women had similar adjusted 2-year ischemic and bleeding outcomes. On the same hand, a pooled analysis of six randomized trials showed that in both sexes short DAPT is associated with similar rates of cardiovascular outcomes but lower risk of bleeding when compared with prolonged DAPT [70].…”
Section: Dual Antiplatelet Therapymentioning
confidence: 99%
“…Multiple randomized clinical trials (RCTs) have evaluated the safety and efficacy of different DAPT durations with conflicting results [12][13][14][15]. Previous meta-analyses and systematic review have also shown mixed results [16][17][18][19]. Therefore, we conducted our network metaanalysis to evaluate the safety and efficacy of various DAPT durations in patients undergoing DES implantation.…”
Section: Introductionmentioning
confidence: 99%